2019
DOI: 10.3389/fmicb.2019.00459
|View full text |Cite
|
Sign up to set email alerts
|

Two Functionally Deviating Type 6 Secretion Systems Occur in the Nitrogen-Fixing Endophyte Azoarcus olearius BH72

Abstract: Type VI protein secretion systems (T6SSs) have been identified in many plant-associated bacteria. However, despite the fact that effector proteins may modulate host responses or interbacterial competition, only a few have been functionally dissected in detail. We dissected the T6SS in Azoarcus olearius strain BH72, a nitrogen-fixing model endophyte of grasses. The genome harbors two gene clusters encoding putative T6SSs, tss-1 and tss-2, of which only T6SS-2 shared genetic organization and functional homology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 68 publications
0
17
0
Order By: Relevance
“…Activity of T6SS can be posttranslationally modulated via a threonine phosphorylation (TPP) dependent (involving TagEGH) [Mougous et al, 2007] and an independent (involving TagF) [Silverman et al, 2011] pathway. The recent study by Jiang et al [2019] revealed the presence of two gene clusters for T6SS in Az. olearius BH72, termed tss-1 and tss-2 ( Fig.…”
Section: Search For Capacities Enabling Azoarcus-like Endophytic Lifementioning
confidence: 99%
See 3 more Smart Citations
“…Activity of T6SS can be posttranslationally modulated via a threonine phosphorylation (TPP) dependent (involving TagEGH) [Mougous et al, 2007] and an independent (involving TagF) [Silverman et al, 2011] pathway. The recent study by Jiang et al [2019] revealed the presence of two gene clusters for T6SS in Az. olearius BH72, termed tss-1 and tss-2 ( Fig.…”
Section: Search For Capacities Enabling Azoarcus-like Endophytic Lifementioning
confidence: 99%
“…petrolei ToN1 T and Ar. bremense PbN1 T was assessed for clues on endophytic lifestyle capacities by searching for the presence of genes required or suspected for Azoarcus-type microbe-plant interaction, i.e., nitrogenase [Egener et al, 1999], type VI protein secretion systems (T6SSs) [Jiang et al, 2019], biosynthesis of indoleacetate [Fernández et al, 2014], pili, flagella, and the TonB-system [Reinhold-Hurek et al, 2006;Böhm et al, 2007;Buschart et al, 2012]. (i) Nitrogenase Diazotrophic microorganisms fix nitrogen mostly by means of molybdenum nitrogenases composed of two protein complexes [for overview refer to Ludden, 2005, 2008].…”
Section: Search For Capacities Enabling Azoarcus-like Endophytic Lifementioning
confidence: 99%
See 2 more Smart Citations
“…However, the researchers could not show involvement in inter-bacterial competition in vitro. The nitrogen fixing bacteria Azoarcus olearius BH72 encodes two T6SS operons, one of which is strongly up-regulated when nitrogen is absent (Jiang et al, 2019). Kosakonia strains are endophytic nitrogen fixers involved in plant growth promotion in rice (Bertani et al, 2016).…”
Section: Root-nodulating Bacteriamentioning
confidence: 99%